Multimodality imaging and transcriptomics to phenotype mitral valve dystrophy in a unique knock-in Filamin-A rat model. Issue 3 (24th August 2022) - Delwarde, Constance; Toquet, Claire; Aumond, Pascal; Kayvanjoo, Amir Hossein; Foucal, Adrien; Le Vely, Benjamin; Baudic, Manon; Lauzier, Benjamin; Blandin, Stéphanie; Véziers, Joëlle; Paul-Gilloteaux, Perrine; Lecointe, Simon; et al.
Abstract: Aims: Degenerative mitral valve dystrophy (MVD) leading to mitral valve prolapse is the most frequent form of MV disease, and there is currently no pharmacological treatment available. The limited understanding of the pathophysiological mechanisms leading to MVD limits our ability to identify therapeutic targets. This study aimed to reveal the main pathophysiological pathways involved in MVD via the multimodality imaging and transcriptomic analysis of the new and unique knock-in (KI) rat model for the FilaminA-P637Q (FlnA-P637Q) mutation associated-MVD. Methods and results: Wild-type (WT) and KI rats were evaluated morphologically, functionally, and histologically between 3-week-old and 3-to-6-month-old based on Doppler echocardiography, 3D micro-computed tomography (microCT), and standard histology. RNA-sequencing and Assay for Transposase-Accessible Chromatin (ATAC-seq) were performed on 3-week-old WT and KI mitral valves and valvular cells, respectively, to highlight the main signalling pathways associated with MVD. Echocardiographic exploration confirmed MV elongation (2.0 ± 0.1 mm vs. 1.8 ± 0.1, P = 0.001), as well as MV thickening and prolapse in KI animals compared to WT at 3 weeks. 3D MV volume quantified by microCT was significantly increased in KI animals (+58% vs. WT, P = 0.02). Histological analyses revealed a myxomatous remodelling in KI MV characterized by proteoglycans accumulation. A persistent phenotype was observed in adult KI rats. Signalling pathways related to extracellular matrix homeostasis, response to molecular stress, epithelial cell migration, endothelial to mesenchymal transition, chemotaxis and immune cell migration, were identified based on RNA-seq analysis. ATAC-seq analysis points to the critical role of transforming growth factor-β and inflammation in the disease. Conclusion: The KI FlnA-P637Q rat model mimics human myxomatous MVD, offering a unique opportunity to decipher pathophysiological mechanisms related to this disease. Extracellular matrix organization, epithelial cell migration, response to mechanical stress, and a central contribution of immune cells are highlighted as the main signalling pathways leading to myxomatous MVD. Our findings pave the road to decipher underlying molecular mechanisms and the specific role of distinct cell populations in this context. Graphical Abstract: Graphical Abstract